Precipitative Coating of Calcium Phosphate on Microporous Silica–Titania Hybrid Particles in Simulated Body Fluid - Reo Kimura; Kota Shiba; Kanata Fujiwara; Yanni Zhou; Iori Yamada; Motohiro Tagaya (Inorganics, 2023)
Titania and silica have been recognized as potential drug delivery system (DDS) carriers. For this application, controllable biocompatibility and the suppression of the initial burst are required, which can be provided by a calcium phosphate (CP) coating. However, it is difficult to control the morphology of a CP coating on the surface of carrier particles owing to the homogeneous nucleation of CP. In this study, we report the development of a CP-coating method that homogeneously corresponds to the shapes of silica–titania (SiTi) porous nanoparticles. We also demonstrate that controlled surface roughness of CP coatings could be achieved in SBF using SiTi nanoparticles with a well-defined spherical shape, a uniform size, and a tunable nanoporous structure. The precipitation of CP was performed on mono-dispersed porous SiTi nanoparticles with different Si/Ti molar ratios and pore sizes. The pore size distribution was found to significantly affect the CP coating in SBF immersion; the surfaces of the nanoparticles with bimodal pore sizes of 0.7 and 1.1–1.2 nm became rough after CP precipitation, while those with a unimodal pore size of 0.7 nm remained smooth, indicating that these two pore sizes serve as different nucleation sites that lead to different surface morphologies.